Pelatihan Penggunaan Aplikasi Mendeley dalam Menyusun Karya Ilmiah bagi Mahasiswa - Mangngassai, Ince Abdul Muhaemin; Wainggai, Heppy Hein; Marsuki, Marsuki; Syaiful, Andi; Widyanto, Zainal; Pusmiati, Pusmiati (J-Abdimas Cenderawasih, 2023)
Higher Education always strives to progress and develop in order to maintain its reputation and improve the achievements to be achieved. One indication of quality writing is related to the element of plagiarism which often occurs due to a person's lack of knowledge about citation techniques or how to do citations. Therefore, students must be given an explanation on how to make good citations in order to produce good and quality scientific work for publication in national/international journals. In managing references sourced from books or journals, this can be done using several available software/applications, such as Mendeley, Endnote, Zootero and others. The existence of software such as Mendeley can be used to assist in writing citations, enabling authors to process reference documents they have. Based on the results of the implementation of the activity, it can be seen that there was an increase in the knowledge and abilities of the participants regarding the Mendeley Application before and after the training. However, in terms of the ability to install applications on laptops and Ms. Word and using the Mendeley application to make a bibliography of some participants were not fully mastered (100%), so they had to be assisted and directed even though the training had been completed.